Genetic determinants of increased body mass index mediate the effect of smoking on increased risk for type 2 diabetes but not coronary artery disease. (24th August 2020) - Thom, Christopher S; Ding, Zhuoran; Levin, Michael G; Damrauer, Scott M; Lee, Kyung Min; Lynch, Julie; Chang, Kyong-Mi; Tsao, Philip S; Cho, Kelly; Wilson, Peter W F; Assimes, Themistocles L; Sun, Yan V; et al.
Abstract: Clinical observations have linked tobacco smoking with increased type 2 diabetes risk. Mendelian randomization analysis has recently suggested smoking may be a causal risk factor for type 2 diabetes. However, this association could be mediated by additional risk factors correlated with smoking behavior, which have not been investigated. We hypothesized that body mass index (BMI) could help to explain the association between smoking and diabetes risk. First, we confirmed that genetic determinants of smoking initiation increased risk for type 2 diabetes (OR 1.21, 95% CI: 1.15–1.27, P = 1 × 10 −12 ) and coronary artery disease (CAD; OR 1.21, 95% CI: 1.16–1.26, P = 2 × 10 −20 ). Additionally, 2-fold increased smoking risk was positively associated with increased BMI ( 0.8 kg/m 2, 95% CI: 0.54–0.98 kg/m 2, P = 1.8 × 10 −11 ). Multivariable Mendelian randomization analyses showed that BMI accounted for nearly all the risk smoking exerted on type 2 diabetes (OR 1.06, 95% CI: 1.01–1.11, P = 0.03). In contrast, the independent effect of smoking on increased CAD risk persisted (OR 1.12, 95% CI: 1.08–1.17, P = 3 × 10 −8 ). Causal mediation analyses agreed with these estimates. Furthermore, analysis using individual-level data from the Million Veteran Program independently replicated the association of smoking behavior with CAD (OR 1.24, 95% CI: 1.12–1.37, P = 2 × 10 −5 ), but not type 2 diabetes (OR 0.98, 95% CI: 0.89–1.08, P = 0.69), after controlling for BMI. Our findings support a model whereby genetic determinants of smoking increase type 2 diabetes risk indirectly through their relationship with obesity. Smokers should be advised to stop smoking to limit type 2 diabetes and CAD risk. Therapeutic efforts should consider pathophysiology relating smoking and obesity.